Changes in blood parameters in patients with diseases of the oral mucosa on the background of oncopathology - O. A. Uspenskaya; I. I. Fadeeva (LLC "Endo Press", 2020)
Study of the dynamics of blood parameters in the disease of the oral mucosa in patients with extraoral oncopathology.Aim. To study the changes in the indicators of the General blood test in patients with diseases of the oral mucosa on the background of cancer.Materials and metods. To perform the study on the basis of the hospitals of THE Nizhny Novgorod regional clinical Oncology dispensary, a survey of the dental status of patients with cancer of various localization was carried out. The study groups included patients compared by age, sex, concomitant dental diseases in remission. The criteria for exclusion from the examination were cancer patients receiving chemotherapy and radiation therapy, patients who refused to participate in the examination and patients with stage 1 and 4 cancer. All subjects underwent a clinical blood test with further investigation.Results. The study included 66 women. There were changes in certain blood parameters depending on localization of the pathology and nosology of dental disease, namely, hematocrit, hemoglobin, the average volume of erythrocytes, the average concentration of hemoglobin in erythrocyte mass, mean content of hemoglobin in a single erythrocyte, the relative width of the distribution of erythrocyte volume, the absolute content of lymphocytes.Conclusions. The study revealed the presence of signs of the initial stage of anemia, which occurs against the background of malignant education.